Mengenal Iblis (Kajian Tafsir Tematik tentang Kesombongan Iblis) - Nasiri . (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
The controversy over the devil as a "convicted" creature, accursed and driven from heavenly pleasures is a dramatic and perennial narrative in every divine religion. Since God proclaimed to create the first ruler of earth (read Adam), the devil not only presents himself as a dissident and seductive creature of Adam and his grandchildren, as the conclusion of the classical and modern interpretations above, but also at the same time the symbol of the negative predisposition or personification of crime. No man is immune to the seduction of the devil, but the devil can not really deceive those who have always maintained their moral integrity from his attacks. The key to the defense of man against the temptations of the devil is the piety of Allah SWT.